Pathogenesis-Related Gene Expression in Response to Trachyspermum ammi Supplementation Along With Probiotics in Chicken Salmonellosis and Insights in Drug Therapeutics - Haq, Zulfqarul; Ahmad, Syed Mudasir; Bashir, Ishrat; Dar, Mashooq Ahmad; Saleem, Afnan; Khan, Azmat Alam; Yatoo, Mohammad Iqbal; Mir, Shabir; Rastogi, Ankur; Hussain, Mohd Isfaqul; Shah, Riaz A.; Bhat, Basharat (Frontiers in Veterinary Science, 2022)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is the leading cause of foodborne illness. Since Salmonella continues to have a detrimental effect on public health, there is an ongoing need to develop more advanced methods for combating Salmonellosis in foods before they reach consumers. The quest for alternative natural products has recently intensified due to increasingly stringent regulations regarding the use of antibiotics as growth promoters, as well as consumer demand for antibiotic-free poultry products. This study was conducted to evaluate the effect of ajwain extract (AJE) on immune response and antioxidant status in broiler chicks challenged with Salmonella Typhimurium. The chicks were infected with S. Typhimurium and were divided into different groups except control group (CON). The challenged chicks received different treatments with 3*109CFU Acipro-WSTM probiotic (PRO), 200mg/Kg Aiwain extract (AJE), 200 mg/100Kg of enrofloxacin (ENR) and combination of 3*109CFU Acipro-WSTM probiotic and 200mg/Kg ajwain extract (COM). Five days’ post treatment the tissue samples (liver and spleen) were analyzed. The results showed that basal diet supplemented with ajwain extract (AJE) and a combination of probiotic and ajwain extract (COM) significantly (P< 0.0.5) reduced the cytokine expression in broiler chicks challenged with S. Typhimurium. Our findings suggest that AJE can clear the bacterial infection, improve antioxidant status as well as suppress the inflammation response. Additionally, AJE supplementation significantly mitigated the S. Typhimurium-induced increases in the interleukin (IL-6) (spleen and liver), IL-8(spleen and liver), IL-17A (spleen and liver), and inducible nitric oxide (iNOS) (spleen and liver) levels (P < 0.05). We concluded that ajwain is a potential feed additive with dual efficacy as an anti- inflammatory and antioxidant agent. The interaction networks developed in the current study provides a novel lead that could targeted for anti-inflammatory and antioxidant property.